Design of PSMA ligands with modifications at the inhibitor part: an approach to reduce the salivary gland uptake of radiolabeled PSMA inhibitors? - Veronika Barbara Felber; Manuel Amando Valentin; Hans-Jürgen Wester (SpringerOpen, 2021)
Abstract Aim To investigate whether modifications of prostate-specific membrane antigen (PSMA)-targeted radiolabeled urea-based inhibitors could reduce salivary gland uptake and thus improve tumor-to-salivary gland ratios, several analogs of a high affinity PSMA ligand were synthesized and evaluated in in vitro and in vivo studies. Methods Binding motifs were synthesized 'on-resin' or, when not practicable, in solution. Peptide chain elongations were performed according to optimized standard protocols via solid-phase peptide synthesis. In vitro experiments were performed using PSMA+ LNCaP cells. In vivo studies as well as μSPECT/CT scans were conducted with male LNCaP tumor xenograft-bearing CB17-SCID mice. Results PSMA ligands with A) modifications within the central Zn2+-binding unit, B) proinhibitor motifs and C) substituents & bioisosteres of the P1'-γ-carboxylic acid were synthesized and evaluated. Modifications within the central Zn2+-binding unit of PSMA-10 (Glu-urea-Glu) provided three compounds. Thereof, only natLu-carbamate I (natLu-3) exhibited high affinity (IC50 = 7.1 ± 0.7 nM), but low tumor uptake (5.31 ± 0.94% ID/g, 1 h p.i. and 1.20 ± 0.55% ID/g, 24 h p.i.). All proinhibitor motif-based ligands (three in total) exhibited low binding affinities (> 1 μM), no notable internalization and very low tumor uptake (< 0.50% ID/g). In addition, four compounds with P1'-ɣ-carboxylate substituents were developed and evaluated. Thereof, only tetrazole derivative natLu-11 revealed high affinity (IC50 = 16.4 ± 3.8 nM), but also this inhibitor showed low tumor uptake (3.40 ± 0.63% ID/g, 1 h p.i. and 0.68 ± 0.16% ID/g, 24 h p.i.). Salivary gland uptake in mice remained at an equally low level for all compounds (between 0.02 ± 0.00% ID/g and 0.09 ± 0.03% ID/g), wherefore apparent tumor-to-submandibular gland and tumor-to-parotid gland ratios for the modified peptides were distinctly lower (factor 8-45) than for [177Lu]Lu-PSMA-10 at 24 h p.i. Conclusions The investigated compounds could not compete with the in vivo characteristics of the EuE-based PSMA inhibitor [177Lu]Lu-PSMA-10. Although two derivatives (3 and 11) were found to exhibit high affinities towards LNCaP cells, tumor uptake at 24 h p.i. was considerably low, while uptake in salivary glands remained unaffected. Optimization of the established animal model should be envisaged to enable a clear identification of PSMA-targeting radioligands with improved tumor-to-salivary gland ratios in future studies.